1993
DOI: 10.1021/jm00057a007
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2-imidazolidinylidene propanedinitrile derivatives as stimulators of gastrointestinal motility. 1

Abstract: Ranitidine (1), the histamine H2-receptor antagonist, has been previously reported to increase gastric emptying and gastric motility by inhibition of acetylcholinesterase (AChE) and enhancement of acetylcholine (ACh) release. In order to obtain potent gastroprokinetic agents, a new series of ranitidine derivatives (5-32) possessing a nitrogen atom instead of a sulfur atom (B) was synthesized and their AChE inhibitory activity and potentiating action on electrically evoked contractions of guinea pig ileum were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…In conclusion, the present study shows that imidazole N-oxides 1 easily react with BTF The formation of 11 under anhydrous conditions can be of preparative importance as derivatives of (1,3-dihydroimidazol-2-ylidene)malononitriles are known as pharmacologically active compounds [25].…”
Section: Methodsmentioning
confidence: 61%
“…In conclusion, the present study shows that imidazole N-oxides 1 easily react with BTF The formation of 11 under anhydrous conditions can be of preparative importance as derivatives of (1,3-dihydroimidazol-2-ylidene)malononitriles are known as pharmacologically active compounds [25].…”
Section: Methodsmentioning
confidence: 61%
“…
ABSTRACT-The effects of [1][2]fumarate, on the loperamide or clonidine-induced delayed propulsion were determined in rats and compared with those of other gastroprokinetic agents. Administration of loperamide (0.3 mg/kg, s.c.) or clonidine (0.01 mg/kg, s.c.) induced delay of the evacuation time of the teflon ball, which had been inserted into the distal colon.
…”
mentioning
confidence: 99%
“…KW-5092 possesses acetyl choline esterase inhibitory activity and exhibits potentiat ing action on electrically evoked contractions of the isolat ed guinea pig ileum (1). Furthermore, KW-5092 enhances motility of the gastric antrum and colon in anesthetized rabbits (1), suggesting that KW-5092 stimulates motility of the alimentary tract in general. Colonic transport activ ity can be estimated by measuring the time required to ex crete a small ball inserted into the colon of mice or rats (2 5).…”
mentioning
confidence: 99%
“…Innervation of the GI tract by the vagus nerve is known to enhance motility ( 42 , 43 ). We reasoned that the enhanced survival following a lethal oral infection in paraoxon-treated mice could be attributed to enhanced intestinal motility that would lead to a faster bacterial clearance from the intestine.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that ACh stimulates gut functions like acid production and intestinal motility ( 51 ). Several studies have shown in vitro ( 52 ) and in vivo ( 42 , 43 ) that AChE inhibitors induce an increase in gastrointestinal motility within minutes or few hours of administration. One possible mechanism by which paraoxon administration improves survival of orally infected animals could be by increasing intestinal motility.…”
Section: Discussionmentioning
confidence: 99%